Ageing in place: re-configuring the home - Spanbroek, Nancy (ISG, Helsinki, Finland, 2005)
In Australia accidents are the major cause of hospitalization for the aged population. The accessible home therefore becomes critical in allowing one to continue to live independently. This can only occur if the home is barrier free and supports physical frailties. Renovations are required in the majority of homes to prepare for an ageing occupant. Simple changes to joinery design can alleviate the potential for accidents and encourage independent living. This paper will present design ideas that support ageing in place.